2010
DOI: 10.1104/pp.110.166470
|View full text |Cite
|
Sign up to set email alerts
|

Two Host Cytoplasmic Effectors Are Required for Pathogenesis of Phytophthora sojae by Suppression of Host Defenses    

Abstract: Phytophthora sojae encodes hundreds of putative host cytoplasmic effectors with conserved FLAK motifs following signal peptides, termed crinkling-and necrosis-inducing proteins (CRN) or Crinkler. Their functions and mechanisms in pathogenesis are mostly unknown. Here, we identify a group of five P. sojae-specific CRN-like genes with high levels of sequence similarity, of which three are putative pseudogenes. Functional analysis shows that the two functional genes encode proteins with predicted nuclear localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
147
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(163 citation statements)
references
References 55 publications
14
147
0
Order By: Relevance
“…We previously demonstrated that PsCRN63 and PsCRN115, although sharing high sequence similarity, have contrasting roles in manipulating plant PCD. Expression of PsCRN63 and PsCRN115 is jointly required for full virulence (Liu et al, 2011). Here, we show that expression of PsCRN63 or PsCRN63/115 together promotes the in planta growth of P. capsici.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…We previously demonstrated that PsCRN63 and PsCRN115, although sharing high sequence similarity, have contrasting roles in manipulating plant PCD. Expression of PsCRN63 and PsCRN115 is jointly required for full virulence (Liu et al, 2011). Here, we show that expression of PsCRN63 or PsCRN63/115 together promotes the in planta growth of P. capsici.…”
Section: Resultsmentioning
confidence: 74%
“…5E), indicating that the suppression of PsCRN63-induced PCD by catalases is specific. We also noticed that PsCRN115 did not suppress PCD triggered by these inducers (Liu et al, 2011), indicating that the catalases and PsCRN115 are specifically involved in regulating the PCD-triggering activity of PsCRN63.…”
Section: Pscrn63 and Pscrn115 Interact With Catalase In The Plant Nucmentioning
confidence: 72%
See 3 more Smart Citations